An Analysis Transformer Oil Temperature A PT. PLN ULP Medan Sunggal Based On Mathlab - Wawan Dermawan; Siti Anisah; Amani Darma Tarigan (Sean Institute, 2024)
Electricity consumption is increasing, this is because consumers are using more and more electric current. As a result, disturbances often occur in the transformer and one of these disturbances is caused by deteriorating insulation. This deteriorating insulation is caused by a lack of monitoring of transformer oil. This research aims to predict the temperature of transformer oil to find out whether the transformer oil is in good, fair or bad condition. The research was carried out by entering breakdown voltage data from PT PLN into the math-lab software using the fuzzy toolbox, then the mathl-ab software will display the temperature level. The results of testing and calculating MPE (Mean Percentage Error) show that the percentage value of correctness for temperature calculations using fuzzy logic is well applied to determine temperature predictions with an average correct value of 83.44% for new oil and 91.852% for used oil.